Current collector, electrode tab, secondary battery, and electric device

CN117317236BActive Publication Date: 2026-10-09BYD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210704116.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-21
Publication Date
2026-10-09
Estimated Expiration
2042-06-21

AI Technical Summary

Technical Problem

可见,电芯在充放电过程中的体积变化率较大,这会导致电池的循环性能较差

Benefits of technology

[0058] To highlight the beneficial effects of this application, the following comparative example 1 is provided for embodiment 1, and the following comparative example 2 is provided for embodiments 4-5.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003705562120000081
    Figure BDA0003705562120000081
  • Figure BDA0003705562120000091
    Figure BDA0003705562120000091
Patent Text Reader

Abstract

The application provides a current collector, an electrode pole piece, a secondary battery and an electric device. The current collector comprises a porous metal framework, and pressure elastic fillers and a binder loaded on the porous metal framework, at least some of the pressure elastic fillers being filled in the pores of the porous metal framework, wherein the pressure elastic fillers are three-dimensional graphenes, the three-dimensional graphenes have a porous structure; after a first pressure of 30-200 Mpa is applied to the current collector in the thickness direction of the current collector, the first pressure is removed, after the thickness of the current collector rebounds stably, a second pressure greater than 0 and less than or equal to 5 Mpa is applied to the current collector in the thickness direction of the current collector, and the stable rebound rate and the stable compression rate of the thickness of the current collector are independently in the range of 3%-50%. The current collector has good compression rebound performance, the volume change rate of the battery cell using the current collector is small in the charging and discharging cycle process, and the cycle performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a current collector, electrode plates, a secondary battery, and an electrical device. Background Technology

[0002] During charging, the negative electrode volume of a lithium-ion battery gradually increases, and the overall cell volume generally also increases. With a fixed cell casing size, the external pressure exerted on the cell by the casing gradually increases as charging progresses. This can easily lead to increased electrode polarization and electrolyte extrusion from the cell. Conversely, during discharging, the negative electrode volume gradually decreases, and the external pressure on the cell gradually decreases. Therefore, the cell exhibits a significant rate of volume change during charging and discharging, resulting in poor battery cycle performance. Summary of the Invention

[0003] In view of this, this application provides a current collector, electrode plates, a secondary battery, and an electrical device. The current collector has good elastic self-recovery properties, which can effectively reduce the volume change rate of the battery cell during the cycle and improve the cycle performance of the battery.

[0004] The first aspect of this application provides a current collector comprising a porous metal skeleton, a pressure-elastic filler and a binder loaded on the porous metal skeleton, wherein at least a portion of the pressure-elastic filler fills the pores of the porous metal skeleton, wherein the pressure-elastic filler is three-dimensional graphene having a porous structure; wherein, after applying a first pressure of 30-200 MPa to the current collector along its thickness direction, the first pressure is removed, and after the thickness of the current collector has rebounded and stabilized, a second pressure greater than 0 and less than or equal to 5 MPa is applied to the current collector along its thickness direction, then the stable rebound rate and stable compression rate of the current collector thickness are independently within the range of 3%-50%.

[0005] In the current collector provided in this application embodiment, the current collector has a certain compressive elasticity due to the addition of three-dimensional graphene to the porous metal framework. For battery systems with large negative electrode volume expansion during charging, the current collector can effectively reduce the volume change rate of the cell during charge and discharge cycles and improve the cycle performance of the battery.

[0006] Secondly, this application provides an electrode plate having a current collector as described in the first aspect of this application. The electrode plate can be a positive electrode plate or a negative electrode plate.

[0007] Because of the use of the aforementioned current collector, the volume change rate of the electrode plates during battery charging and discharging is reduced, which helps to improve the battery's cycle performance.

[0008] Thirdly, this application provides a secondary battery comprising electrode plates as described in the first aspect of this application. The positive electrode plate of the secondary battery has the aforementioned current collector, and / or the negative electrode plate has the aforementioned current collector.

[0009] Due to the use of the aforementioned electrode plates, the volume change rate of the secondary battery cell during charging and discharging is effectively reduced, and the cycle performance of the battery is improved.

[0010] Fourthly, this application provides an electrical device that includes a secondary battery as described in the third aspect of this application. Detailed Implementation

[0011] The technical solutions of the embodiments of this application will be described in detail below.

[0012] This application provides a current collector comprising a porous metal skeleton, a pressure-elastic filler, and a binder loaded on the porous metal skeleton. At least part of the pressure-elastic filler is filled in the pores of the porous metal skeleton. The pressure-elastic filler is three-dimensional graphene with a porous structure. After applying a first pressure of 30-200 MPa to the current collector along its thickness direction, the first pressure is removed. After the thickness of the current collector has rebounded and stabilized, a second pressure greater than 0 and less than or equal to 5 MPa is applied to the current collector along its thickness direction. The stable rebound rate and stable compression rate of the current collector thickness are independently within the range of 3%-50%.

[0013] The porous metal skeleton of the current collector provided in this application embodiment introduces three-dimensional graphene with the above-mentioned properties and a binder. The binder helps to ensure the stable adhesion of the three-dimensional graphene to the porous metal skeleton. Because the three-dimensional graphene has a certain compressive elasticity, it can shrink in volume under greater pressure and gradually recover its volume when there is no pressure or the pressure decreases. Thus, the current collector also has an elastic self-recovery function.

[0014] Specifically, as the battery charges, Li + As the negative electrode gradually integrates, its volume gradually increases, generally leading to an increase in the overall cell volume. This expansion is particularly pronounced in battery systems with large negative electrode expansion (such as silicon-based materials and lithium metal). With a fixed cell casing size, the gradually increasing cell size experiences increasing external pressure from the casing as charging progresses. This pressure is transmitted to the current collector, where the compressive elastic filler contracts along with the porous three-dimensional framework, gradually reducing the current collector's thickness. This releases some space, mitigating the overall cell volume expansion caused by the negative electrode expansion and minimizing significant increases in cell volume during charging. When the battery discharges, as the Li...+ As the electrolyte dissolves from the negative electrode and re-intercalates into the positive electrode, the volume of the negative electrode gradually decreases. This reduces the external pressure on the cell from the casing, causing the filler, with its compressive elasticity, to gradually rebound. This rebound increases the volume of the entire current collector, compensating for the overall cell volume shrinkage caused by the negative electrode contraction. This prevents significant shrinkage of the cell volume during discharge. Therefore, the aforementioned elastic current collector effectively reduces the rate of volume change of the cell during charge-discharge cycles, stabilizes the distance between the positive and negative electrode surfaces, reduces the probability of polarization of the electrode active materials and electrolyte extrusion from the cell during charging, thereby improving the battery's cycle performance.

[0015] Specifically, controlling the stable rebound rate and stable compression rate of the current collector thickness independently within the range of 3%-50% can reduce the volume change rate of the cell during charge-discharge cycles, stabilize the distance between the positive and negative electrode surfaces, and reduce the probability of polarization of the electrode active materials and electrolyte extrusion from the cell during charging, thereby improving the battery's cycle performance. If the stable rebound rate and stable compression rate are below the above range, it means that the compression additive is insufficient to reduce the volume change rate of the cell during charge-discharge cycles, stabilize the distance between the positive and negative electrode surfaces, and reduce the probability of polarization of the electrode active materials and electrolyte extrusion from the cell during charging, resulting in no significant improvement in battery cycle performance. If the stable rebound rate and stable compression rate are above the above range, it means that the content of the compression additive is too high or the structural stability of the compression additive is poor, resulting in poor current collector stability and decreased battery cycle stability.

[0016] Furthermore, when the aforementioned current collector is used as a substrate for lithium metal deposition (such as as a negative electrode current collector for lithium metal batteries or negative electrodeless batteries), during the charging process of the battery, the aforementioned pressurized filler will guide lithium deposition in the pores near the pressurized filler to suppress lithium dendrite growth.

[0017] The first pressure of 30-200 MPa mentioned above refers to the pressure that the current collector may withstand during the preparation of the electrode sheet using this current collector. The second pressure, greater than 0 and less than or equal to 5 MPa, refers to the pressure that the battery cell may withstand during battery charge-discharge cycles, i.e., the possible pressure conducted to the current collector. In some embodiments, this second pressure may be 0.1-1 MPa. The above two thickness change rate parameters of the current collector indicate that the current collector has excellent compression-rebound performance, which can effectively reduce the volume change rate of the electrode sheet during cycling, thereby improving the cycle performance of the battery. The stable rebound rate and stable compression rate of the current collector thickness may be equal or different. The test methods for these two parameters can be found in the description below in this application.

[0018] The test method for the stable rebound rate of the current collector thickness is as follows: First, apply a first pressure of X2 MPa parallel to the thickness direction to the current collector, then remove the first pressure. After the current collector thickness has rebounded and stabilized, apply a second pressure of X3 MPa parallel to the thickness direction to the current collector, and measure the thickness H3 of the current collector under the X3 MPa pressure. Then, remove the second pressure, and after the current collector thickness has rebounded and stabilized, measure the thickness H4 of the current collector. The stable rebound rate of the current collector thickness is then r2 = (H4 - H3) / H3. Here, the value range of X2 is 30-200 MPa, and the value range of X3 is 0 < X3 ≤ 5 MPa.

[0019] The test method for the stable compressibility of the current collector thickness is as follows: First, apply a first pressure of X4 MPa parallel to the thickness direction to the current collector, then remove the first pressure. After the current collector thickness rebounds and stabilizes, record the current collector thickness as H5. Then, apply a second pressure of X5 MPa parallel to the thickness direction to the current collector and measure the current collector thickness H6 under the second pressure of X5 MPa. The stable compressibility of the current collector thickness is then p = (H5 - H6) / H5. Where X4 ranges from 30 to 200 MPa, and X5 ranges from 0 to 5 MPa.

[0020] Furthermore, after applying a first pressure of 30-200 MPa to the aforementioned current collector and then removing it, the initial rebound rate of the current collector thickness can be between 5% and 95%. The pressure range of 30-200 MPa is a common rolling pressure range when using this current collector to manufacture electrode sheets. This initial rebound rate indicates that the current collector can rebound well after rolling, allowing it to better play its role in reducing volume changes in the battery cell during cycling after the electrode sheets are manufactured. The test method for the initial rebound rate of the current collector thickness is as follows: Apply a first pressure of X1 MPa parallel to the thickness direction to the current collector, and measure the thickness of the current collector under the X1 MPa pressure as H1; then remove the pressure, and after the thickness of the current collector stabilizes, measure the thickness of the current collector again, denoted as H2. The initial rebound rate of the current collector thickness is then r1 = (H2 - H1) / H1. Here, the value of X1 ranges from 30-200 MPa.

[0021] In this application, the porous structure of three-dimensional graphene is formed by overlapping graphene sheets. The maximum pore size of this porous structure does not exceed 200 nm. The maximum pore size refers to the diameter of the largest pore in the porous structure, and "pore size" can refer to the maximum width of each pore. Since the maximum pore size does not exceed 200 nm, it can be understood that the pore size of each pore in the porous structure does not exceed 200 nm. The smaller pore size helps ensure that the three-dimensional graphene is not prone to structural collapse after being subjected to a certain pressure, and facilitates its rebound. In some embodiments of this application, the average pore size of the porous structure is 10-150 nm. Specifically, the average pore size can be 20 nm, 50 nm, 60 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, etc. The smaller average pore size helps ensure that the current collector containing the three-dimensional graphene is not prone to structural collapse after being subjected to a certain pressure, and facilitates its rebound.

[0022] In this embodiment of the application, the tensile strength at the overlap of the interlocking graphene sheets in the three-dimensional graphene is 20-50 N / m. This indicates that the three-dimensional graphene has high structural stability, and even at the slightly weaker graphene sheet overlaps, the mechanical strength remains high. This ensures that the three-dimensional graphene is not prone to structural collapse under certain external forces, and can therefore be repeatedly compressed and rebounded.

[0023] The parameter "fracture strength at the joint of overlapping graphene sheets" can be obtained by performing nanoindentation tests on the joint of three-dimensional graphene using atomic force microscopy (AFM). The specific testing method is as follows: Three-dimensional graphene is fixed onto a silicon wafer with small holes on its surface. A probe is used to apply pressure to the graphene sheet in the holes, with the pressure applied near the joint of two adjacent graphene sheets. The critical pressure required to cause the joint of the two graphene sheets to fracture is recorded, thus obtaining the fracture strength at the joint between the graphene sheets.

[0024] In this embodiment, the lateral dimensions of the graphene sheets constituting the three-dimensional graphene are in the nanometer range, for example, 10-100 nm, such as 10 nm, 15 nm, 18 nm, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, 90 nm, etc. Preferably, the lateral dimensions of the graphene sheets are 10 nm-30 nm, and more preferably 10 nm-20 nm. Here, the lateral dimensions refer to the length or width of the graphene sheets, which can be obtained from electron microscope images of the three-dimensional graphene. The graphene sheets can be single-layer graphene and / or multi-layer graphene. Controlling the lateral dimensions of the graphene sheets within the above range is mainly to control the pore size formed by the overlap between the graphene sheets and the pore volume of the three-dimensional graphene within a suitable range. The pore size and pore volume of the three-dimensional graphene, together with the fracture strength at the overlap of the graphene sheets, affect the compressive resilience of the three-dimensional graphene material.

[0025] In this embodiment, the average particle size of the three-dimensional graphene is 1-50 μm. Three-dimensional graphene with an average particle size within this range can match the pore structure of common porous metal frameworks, facilitating its uniform filling within the porous metal framework and exhibiting good adhesion, thereby giving the aforementioned current collector good elastic self-healing properties. Specifically, the average particle size of the three-dimensional graphene can be 1.2 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, or 45 μm, etc.

[0026] In this embodiment of the application, the pore volume of the three-dimensional graphene is 1-10 cm³. 3 The pore volume is between / g. This pore volume can be measured using nitrogen adsorption on three-dimensional graphene. Three-dimensional graphene with a pore volume in this range has more micropores, good compressibility, and good resilience, i.e., it has reciprocating compression-resilience.

[0027] In this application, the aforementioned three-dimensional graphene can be grown using plasma chemical vapor deposition (PECVD). An exemplary preparation method includes the following steps: a mixed gas of carbon source (e.g., C2H2) and H2 is introduced into a deposition chamber heated to a certain temperature in a plasma deposition apparatus; a plasma generator is activated to deposit and grow three-dimensional graphene material on a substrate (e.g., Cu) placed in the deposition chamber via PECVD; after the growth of the three-dimensional graphene is complete, an auxiliary gas (e.g., Ar, He) is introduced to cool the deposition chamber to room temperature under an inert atmosphere; the resulting sample is then removed from the deposition chamber, and the three-dimensional graphene material is peeled off from the substrate and broken down to the desired particle size. The PECVD process generates high-energy-density and large-volume plasma, which can decompose the carbon source C2H2 into numerous carbon-containing reactive radicals, thereby achieving the growth of three-dimensional graphene. In some embodiments, the flow rate of C2H2 is 20 mL / min, the flow rate of H2 is 250 mL / min, the deposition growth temperature can be 950 °C, the flow rate of the auxiliary gas Ar is 200 mL / min, and the operating power of the plasma generator is 300 W.

[0028] In this application, at least some compression filler is filled in the pores of the porous metal framework. The compression filler distributed in the pores of the porous metal framework increases the mechanical strength of the framework, maintains its three-dimensional porous structure under pressure, and imparts a certain degree of compressive resilience to the current collector, allowing it to rebound well under pressure. Furthermore, the current collector exhibits good electrical conductivity. In addition, when used as the negative electrode current collector for lithium metal deposition, it effectively guides lithium deposition into the pores of the porous metal framework, reducing the probability of lithium dendrite growth.

[0029] Accordingly, at least some binder is distributed in the pores of the porous metal framework. The presence of the binder can improve the stability of the three-dimensional graphene in the porous metal framework, especially ensuring its adhesion stability in the pores of the porous metal framework, so as to ensure that the current collector has stable elastic self-healing properties.

[0030] In this embodiment, the mass of the elastic filler accounts for 1%-150% of the mass of the porous metal skeleton, preferably 5%-130%. This helps ensure that the current collector exhibits good elastic self-recovery properties. Specifically, the mass of the elastic filler can be 8%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 80%, 100%, 110%, or 140% of the mass of the porous metal skeleton. Further, the mass of the elastic filler filling the pores of the porous metal skeleton accounts for 2%-100% of the total mass of the elastic filler.

[0031] In this embodiment, the binder can account for 0.1%-20% of the mass of the three-dimensional graphene. This ensures good stability of the three-dimensional graphene within the porous metal framework. Specifically, the binder can account for 0.2%, 0.5%, 1%, 2%, 3%, 5%, 10%, 12%, 15%, 18%, etc., of the porous metal framework. In some embodiments, the binder can account for 2%-15% of the mass of the porous metal framework, more preferably 2%-10%.

[0032] In this application, the binder may be independently selected from one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefins (such as polyethylene, polypropylene, polystyrene, etc.), sodium carboxymethyl cellulose (CMC), sodium alginate, etc., but is not limited thereto. The type of binder may be selected depending on whether the current collector is specifically used as a positive electrode current collector or a negative electrode current collector. For example, when the current collector is specifically used as a positive electrode current collector, the binder may be PVDF, PTFE, etc.; when the current collector is specifically used as a positive electrode current collector, the binder may be SBR, CMC, PAA, sodium alginate, etc.

[0033] In this application, the porous metal framework can be various metallic materials with porous structures, including but not limited to elemental metals such as Ni, Cu, Al, Fe, Cr, Au, or Ag, or alloys of the above elements. Specifically, when the current collector is used as a positive electrode current collector, the porous metal framework can be aluminum foam or porous aluminum foil; when the current collector is used as a negative electrode current collector, the porous metal framework can be copper foam, nickel foam, porous copper foil, or porous nickel foil.

[0034] In this embodiment, the porosity of the porous metal skeleton can be 10%-95%, specifically 20%, 30%, 50%, 60%, 70%, 80%, 95%, etc. In some embodiments, the porosity of the porous metal skeleton can be 50%-90%.

[0035] This application also provides an electrode sheet including the current collector described above. The electrode sheet using the current collector can be a positive electrode sheet or a negative electrode sheet. In other words, the current collector can specifically be used as a positive current collector or a negative current collector.

[0036] The electrode generally includes the aforementioned current collector and an electrode active material layer located on the surface of the current collector. If the electrode is a positive electrode, the electrode active material layer is specifically a positive electrode active material layer; if the electrode is a negative electrode, the electrode active material layer is specifically a negative electrode active material layer.

[0037] This application also provides a secondary battery, which includes the electrode plates described above in this application embodiment. The positive electrode plate and / or negative electrode plate of the secondary battery may have the aforementioned current collector.

[0038] In some embodiments of this application, the secondary battery is a lithium-ion battery.

[0039] For solid-state or semi-solid-state batteries, the secondary battery generally includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive and negative electrode, and the positive and negative electrode contain solid or semi-solid electrolyte.

[0040] For secondary batteries with a liquid electrolyte, the battery typically includes a positive electrode, a negative electrode, a separator, and an electrolyte solution positioned between the positive and negative electrodes. The separator separates the positive and negative electrodes, maintaining their insulation and liquid retention properties. Together with the positive and negative electrodes, the separator forms the battery cell, which is housed within the battery casing. The separator can be a polymer separator, non-woven fabric, or other commonly used battery separators, including but not limited to single-layer PP (polypropylene) film, single-layer PE (polyethylene) film, double-layer PP / PE, double-layer PP / PP, and triple-layer PP / PE / PP separators. The electrolyte solution includes electrolyte salts and organic solvents. The specific types and compositions of the electrolyte salts and organic solvents are standard choices in the battery industry and can be selected based on actual needs. The battery casing can be made of aluminum-plastic film, copper-plastic film, steel-plastic film, or other packaging films, and can also be an aluminum casing, steel casing, etc., depending on the type of battery.

[0041] This application also provides an electrical device equipped with the secondary battery described in this application. The electrical device can be a means of transportation, such as a vehicle or ship, or a 3C product.

[0042] The technical solution of this application will be further described below with reference to several specific embodiments.

[0043] Example 1

[0044] A method for preparing a current collector includes the following steps:

[0045] Three-dimensional graphene with a D50 of 20 μm was added to an aqueous solution of polyacrylic acid with a solid content of 5%, wherein the total mass ratio of the three-dimensional graphene to the polyacrylic acid in the polyacrylic acid solution was 100:3. After mixing evenly, water was added to adjust the viscosity of the mixture to 1500 mPa·s. Then, copper foam with a porosity of 95% was immersed in the above mixture. After 5 minutes, the copper foam was removed, dried, and the desired current collector sample was obtained, which can be used as a negative electrode current collector. The total mass of the three-dimensional graphene in the obtained current collector was 130% of the mass of the copper foam.

[0046] In Example 1, the three-dimensional graphene used had an average particle size of 20 μm and a pore volume of 8 cm³. 3 / g, the average pore size of the porous structure in this three-dimensional graphene is 100nm; the fracture strength of the joint of the graphene sheets that overlapped together in the three-dimensional graphene was measured to be 45N / m by nanoindentation test by AFM.

[0047] Example 2

[0048] A method for preparing a current collector includes the following steps:

[0049] Three-dimensional graphene with a D50 of 5 μm was added to an aqueous solution of polyacrylic acid with a solid content of 5%, wherein the mass ratio of three-dimensional graphene to polyacrylic acid in the polyacrylic acid solution was 100:6. After mixing evenly, water was added to adjust the viscosity of the mixture to 1500 mPa·s. Then, a porous copper foil with a thickness of 10 μm and a porosity of 50% was immersed in the above mixture (wherein, the total mass of three-dimensional graphene was 6% of the mass of the porous copper foil). After 5 minutes, the porous copper foil was removed, dried, and the desired current collector sample was obtained, which can be used as a negative electrode current collector.

[0050] In Example 2, the three-dimensional graphene used comprises overlapping graphene sheets and has a porous structure. The average pore size of the porous structure of this three-dimensional graphene is 50 nm, and the pore volume is 5 cm³. 3 / g; The fracture strength of the joint of the graphene sheets that are interlocked in the three-dimensional graphene was measured to be 35 N / m by nanoindentation test by AFM.

[0051] Example 3

[0052] The difference between Example 3 and Example 1 is that the copper foam used has a porosity of 85%, and the total mass of three-dimensional graphene in the obtained current collector sample is 35% of the mass of copper foam.

[0053] Example 4

[0054] A method for preparing a current collector includes the following steps:

[0055] Three-dimensional graphene with a D50 of 10 μm (with the same relevant characteristic parameters as in Example 2) and binder PVDF were added to N-methylpyrrolidone (NMP) at a mass ratio of 100:5. After stirring evenly, a mixed slurry with a viscosity of 1500 mPa·s was obtained. Then, aluminum foam with a porosity of 85% was immersed in the above mixed slurry (the mass of the three-dimensional graphene was 120% of the mass of the aluminum foam). After 5 minutes, the aluminum foam was removed, dried, and the desired current collector sample was obtained, which can be used as a positive electrode current collector.

[0056] Example 5

[0057] The difference between Example 5 and Example 4 is that the D50 particle size of the three-dimensional graphene is 1 μm, and its mass is 125% of the mass of aluminum foam.

[0058] To highlight the beneficial effects of this application, the following comparative example 1 is provided for embodiment 1, and the following comparative example 2 is provided for embodiments 4-5.

[0059] Comparative Example 1

[0060] Untreated copper foam with a porosity of 95% was used directly as the negative electrode current collector.

[0061] Comparative Example 2

[0062] Untreated aluminum foam with 85% porosity was used directly as the positive electrode current collector.

[0063] For each example of current collector sample, the initial rebound rate of thickness, as well as the stable rebound rate and stable compression rate of thickness, were tested. The specific test methods can be found in the previous description of this application, where X1 = 100 MPa, X2 = 60 MPa, X3 = 0.5 MPa, X4 = 60 MPa, and X5 = 0.5 MPa.

[0064] Table 1

[0065]

[0066]

[0067] As can be seen from the comparison between Example 1 and Comparative Example 1 in Table 1, and the comparison between Examples 4-5 and Comparative Example 2, compared with the direct use of untreated porous metal as a current collector, the current collector prepared by soaking the porous metal skeleton in a mixed slurry containing three-dimensional graphene and binder in the embodiments of this application has significantly improved compression performance and resilience performance.

[0068] The negative electrode and battery are fabricated using the current collectors of Examples 1-3 of this application, specifically including the following steps:

[0069] (1) Graphite, silicon suboxide, conductive agent (specifically carbon nanotubes), and binder (specifically polyacrylic acid) are mixed in water at a mass ratio of 90:10:3:4 to prepare a negative electrode slurry. The negative electrode slurry is coated on the current collector samples of Examples 1-3 and the foamed copper foil of Comparative Example 1. After drying and rolling at 50 MPa, a negative electrode sheet is obtained.

[0070] (2) Provide a positive electrode sheet. The specific manufacturing steps include: mixing NCM811 with conductive agent and binder in a mass ratio of 100:1.5:3 in the solvent N-methylpyrrolidone (NMP) to prepare a positive electrode slurry, coating the positive electrode slurry onto aluminum foil, and then drying and rolling it to form a positive electrode sheet.

[0071] (3) Battery assembly: The above-mentioned negative electrode sheet, PE separator, and positive electrode sheet are stacked in sequence to form a battery cell. After injecting electrolyte, the cell is sealed in an aluminum-plastic film. After high-temperature aging, formation, aging, and capacity testing, it is vacuum sealed to obtain a full battery. The negative electrode capacity and the positive electrode capacity are assembled according to an N:P ratio of 1.1.

[0072] Each fabricated full cell was placed in a fixture, with the gap between the fixture and the cell being 2% of the cell thickness. The fixture position was fixed, and each full cell underwent charge-discharge cycle testing. The voltage range was 2.75V-4.25V, the charge rate was 0.5C, and the discharge rate was 1C. The results are summarized in Table 2 below. Capacity retention after 300 cycles = (Discharge capacity after 300 cycles / Initial discharge capacity) * 100%.

[0073] Table 2

[0074] Example 1 92.5% Example 2 87.7% Example 3 90.3% Comparative Example 1 85.1%

[0075] As can be seen from Table 2, for battery systems with large cell expansion during cycling, the current collector with good compressive elasticity proposed in this application can significantly improve the cycle performance of the battery by utilizing the buffering capacity of the current collector for the cell volume expansion.

[0076] Furthermore, using the current collectors of Examples 1-3 of this application in the fabrication of a negative electrode-free battery specifically includes the following steps:

[0077] (1) Provide a positive electrode sheet. Mix NCM811 with conductive agent and binder in solvent N-methylpyrrolidone (NMP) at a mass ratio of 100:1.5:3 to prepare a positive electrode slurry. Coat the positive electrode slurry onto aluminum foil, and after drying and rolling, prepare a positive electrode sheet.

[0078] (2) The current collector samples of Examples 1-3 were pressed by a pressure roller at 50MPa, and then stacked with PE separator and positive electrode sheet to form a battery cell. After being injected with electrolyte, the cells were sealed in an aluminum-plastic film. After high-temperature aging, formation, aging, and capacity testing, the cells were finally vacuum sealed to obtain a negative electrode-free battery.

[0079] The fabricated negative electrode-free battery was placed in a fixture, with the gap between the fixture and the battery being 2% of the battery thickness. The fixture was kept in the same position, and each battery underwent charge-discharge cycle testing. The fabricated batteries were cycled at 0.1C charge and 0.2C discharge within a voltage range of 4.25-3.6V. The relevant results are summarized in Table 3 below.

[0080] Table 3

[0081] Example 1 86.6% Example 2 82.1% Example 3 84.5% Comparative Example 1 78.2%

[0082] As can be seen from Table 3, for batteries without a negative electrode, using the current collector with good compressive elasticity proposed in this application as the negative electrode current collector can also improve the battery cycle performance.

[0083] In addition, the full battery and the negative electrode-free battery that have undergone the above charge-discharge cycle test were disassembled, and the current collector containing the compression filler obtained from the disassembly was subjected to a thickness stability rebound rate and stability compressibility test. The specific test method can be found in the description above in this application. The stability rebound rate r2' and stability compressibility p' of the current collector that have undergone the above charge-discharge cycle test were measured. The difference between r2' and p' and r2 and p in Table 1 is within ±15% (the formulas for calculating the difference between stability rebound rate and stability compressibility are (r2'-r2) / r2 and (p'-p) / p, respectively).

Claims

1. A current collector for use in a secondary battery, characterized in that, The current collector comprises a porous metal skeleton, a pressure-elastic filler, and a binder loaded on the porous metal skeleton. At least a portion of the pressure-elastic filler and at least some of the binder fill the pores of the porous metal skeleton. The pressure-elastic filler is three-dimensional graphene, which has a porous structure formed by overlapping graphene sheets. The tensile strength at the overlap of the overlapping graphene sheets is 20-50 N / m. The maximum pore size of the porous structure does not exceed 200 nm, and the pore volume of the three-dimensional graphene is 1-10 cm³. 3 The mass of the compression filler is between 1% and 150% of the porous metal skeleton, and the mass of the binder is between 0.1% and 20% of the mass of the three-dimensional graphene. Specifically, after applying a first pressure of 30-200 MPa to the current collector along its thickness direction, the first pressure is removed. After the thickness of the current collector has rebounded and stabilized, a second pressure greater than 0 and less than or equal to 5 MPa is applied to the current collector along its thickness direction. Then, the stable rebound rate and stable compression rate of the current collector thickness are independently within the range of 3% to 50%.

2. The current collector as described in claim 1, characterized in that, The lateral dimensions of the graphene sheet are 10nm-100nm.

3. The current collector as described in claim 2, characterized in that, The graphene sheet has a lateral dimension of 10nm-30nm.

4. The current collector according to any one of claims 1-3, characterized in that, The average particle size of the three-dimensional graphene is 1-50µm.

5. The current collector as described in any one of claims 1-3, characterized in that, The mass of the compression filler is 5%-130% of the porous metal skeleton; the mass of the binder is 2%-15% of the mass of the three-dimensional graphene.

6. The current collector as described in claim 4, characterized in that, The mass of the compression filler is 5%-130% of the porous metal skeleton; the mass of the binder is 2%-15% of the mass of the three-dimensional graphene.

7. An electrode sheet, characterized in that, The electrode plate includes the current collector as described in any one of claims 1-6.

8. A secondary battery, characterized in that, The secondary battery includes the electrode plates as described in claim 7.

9. An electrical appliance, characterized in that, The electrical equipment includes the secondary battery as described in claim 8.

Citation Information

Patent Citations

  • Porous metal / three-dimensional graphene composite material

    CN110246702A